Evaluation of cesium removal from radioactive waste water using maghemite PVA-alginate beads - Majidnia, Zohreh (Elsevier, 2015)
The management of radioactive wastes is receiving much attention because radioactive wastes are a threat to people and environment. Cesium which is a component of nuclear waste contributes to water pollution. In this research, maghemite nanoparticles was prepared by the chemical co-precipitation of Fe2+ and Fe3+ and embedded in PVA and alginate matrix and then used in the removal of Cs+ from the aqueous solution. Several parameters like pH, contact time and initial ion concentration were varied so as to determine its influence on the adsorption performance. The findings revealed that Cs+ was removed rapidly under sunlight; where 70% was removed during the first 30min and finally 91% of Cs ions was removed after 300min, hence the term photoadsorption best described its mechanism. Several adsorption kinetic models such as Langmuir and Freundlich isotherm equation, pseudo first-order and pseudo second order were then used to describe the photoadsorption of Cs (I). After photo adsorption the maghemite PVA-alginate beads can be easily isolated from aqueous solution by means of a magnet and reused for at least eight times without losing its initial properties.